2016
DOI: 10.3747/co.23.2846
|View full text |Cite
|
Sign up to set email alerts
|

Involved-Field Irradiation in Definitive Chemoradiotherapy for T4 Squamous Cell Carcinoma of the Esophagus

Abstract: Objectives Definitive concurrent chemoradiotherapy (ccrt) is currently a therapeutic option for locally advanced esophageal cancer. However, clinical practice differs with respect to the target volume for irradiation. The purpose of the present study was to analyze failure patterns and survival, and to determine the feasibility of using involved-field irradiation (ifi) with concurrent chemotherapy for T4 squamous cell carcinoma (scc) of the esophagus.Methods Between January 2003 and January 2013, 56 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…We found that patients with T4 tumors experienced a clinical complete response (cCR) of 0%‐39% and an overall response rate (both complete and partial responses) of 57%‐88% (Table ) . In contrast, the 1‐, 3‐, and 5‐year overall survival (OS) rates of patients with T4 esophageal cancer that received dCRT were 26%‐79%, 0%‐44%, and 0%‐14%, respectively . Seto et al examined prognosis according to the response to CRT; they reported that the 1‐, 3‐, and 5‐year survival rates of patients that experienced cCR and non‐cCR were 83%, 33%, 33%, and 23%, 0%, 0%, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that patients with T4 tumors experienced a clinical complete response (cCR) of 0%‐39% and an overall response rate (both complete and partial responses) of 57%‐88% (Table ) . In contrast, the 1‐, 3‐, and 5‐year overall survival (OS) rates of patients with T4 esophageal cancer that received dCRT were 26%‐79%, 0%‐44%, and 0%‐14%, respectively . Seto et al examined prognosis according to the response to CRT; they reported that the 1‐, 3‐, and 5‐year survival rates of patients that experienced cCR and non‐cCR were 83%, 33%, 33%, and 23%, 0%, 0%, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…As summarized in Tables and , a total of 16 studies examined the outcome of patients with T4 esophageal cancer after dCRT. Two major clinical studies on dCRT for esophageal cancer conducted in Japan, termed JCOG9516 and JCOG0303, were carried out primarily by the Japanese Clinical Oncology Group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations